Cold-Sensitive Corneal Afferents Respond to a Variety of Ocular Stimuli Central to Tear Production: Implications for Dry Eye Disease - Hirata, Harumitsu; Meng, Ian D. (Investigative ophthalmology & visual science, 2010)
To investigate the response characteristics of the corneal afferents that detect ocular conditions critical to the activation of the "afferent limb" of the lacrimation reflex. In isoflurane-anesthetized male rats, trigeminal ganglia were explored extracellularly in vivo to identify the corneal neurons that can be activated by ocular stimuli important to lacrimation. After verifying their receptive field loci to be restricted to the cornea, neural response properties were characterized with a variety of stimuli, such as drying and wetting of the cornea, by applying and removing artificial tears, temperature changes (35 degrees C-15 degrees C and 39 degrees C-51 degrees C), menthol (10-100 microM), and hyperosmolar solutions (NaCl, sucrose; 297-3014 mOsm), applied to the ocular surface. A specific type of corneal afferent was identified that responded to drying of the ocular surface. These neurons were classified as innocuous "cold" thermoreceptors by their responses to steady state and dynamic temperature changes applied to the cornea. In addition to drying and slight cooling (<1 degree C) of the corneal surface, these neurons were excited by evaporation of tears from the ocular surface and hyperosmolar tears. Moreover, these neurons were activated by noxious thermal stimulation and menthol applied to the corneal surface. These results demonstrate that innocuous "cold" cornea thermoreceptors are activated by drying of the ocular surface and hyperosmotic solutions, conditions that are consistent with a role in tear production. The authors hypothesize that the dysfunction of these corneal afferents and the lacrimation reflex pathway they activate lead to some forms of dry eye disease.